An Evaluation Of Student's Perception Towards Learning Physics At Lower Secondary School - Wafry Khairul Ziad; Muhammad Fadhly Ahlamie Md Nor’Azam; Hatika Kaco; Fadzidah Mohd Idris; Siti Munirah Mohd; Nur Hidayah Mohamad Jan; Nor Raihan Zulkefly (UPSI Press, 2024)
Currently, there are emerging concerns about Physics education due to the deteriorate affection in physics subject among the secondary school students. This study aimed to evaluate student’s perception towards their passion on physics education which concentrated on pedagogical approach, nature of physics subject, difficulty level of physics topic and student’s factor. A survey questionnaire was executed to 146 gifted students in Nilai, Negeri Sembilan, Malaysia which were studied physics starting at lower secondary school. Students were found to have different ways in leaning style in which teachers mayuse differentiated learning method to separate between different student’s intelligences based on cognitive level and different suitable assessment. In addition, 90% of the students agreed that the nature of physics topics induced the difficulty of physics. Despite the difficulty nature of physics with enclosed by awfully tough topics, however some topics were easily learnt by the students. Interestingly, 49% realized that physics is important subject to be learnt and yet, 48% of the students disagree thatthey are not doing homework which indicated that most of the students only study while doing their homework. This justified the 68.5% of students spend their time for learning physics in the range of 0-4 h a week just to complete their homework. Ultimately, these finding will give some awareness and advice to the teachers to change teacher’s learning style and boost student’s interest in learning physics. Consequently, their knowledge serves as the backbone for science and technology.